POSSIBILITIES OF CLUSTER ANALYSIS IN Q-METHODOLOGY - CHRASKA, Miroslav (Trends in education, 2014)
The paper introduces the possibilities of using cluster analysis in the processing of research conducted using Q-methodology. The research has examined the importance attributed to individual teachers ICT knowledge and skills of pupils in this area. It was found that teachers can be divided into three distinct groups.
Keywords: cluster analysis; Q-methodology; ICT teacher.